El error de tipo en el delito de estupro debe considerarse como una circunstancia para atenuar la pena de la persona procesada - Cango Zhingre, Andy Joel (2022)
The present thesis entitled: "The error of type in the crime of statutory rape should be considered as a circumstance to mitigate the penalty of the person prosecuted", has its basis of development in that, currently adolescents supported by their physical appearance, digital media, the debauchery that is present in society and motivated by reasons of infatuation, affective and economic enter into a sentimental and sexual relationship with a person of legal age, deceiving about their true age for the effect, tending in the future that a criminal trial for the crime of statutory rape is initiated against the person of legal age. The development of this thesis showed that some adolescents between 14 and 18 years of age may voluntarily place themselves in situations where the violation of their rights is facilitated by ill-intentioned people or lack of due care, where the doctrine, specifically from the field of Victimology has determined as "voluntary victim" and to such appreciation this discipline has said "the active subject is due a reduction of his penalty". It should be clarified that the adolescent, although imprudently placed in such a situation, no subject can use such cause to propitiate a criminal act, in this regard, the Ecuadorian criminal legislation clearly typifies that the consent of the victim is not important in sexual crimes in Article 175, paragraph 5 of the Organic Integral Penal Code. However, in support for the reduction of the penalty of the active subject in the crime of statutory rape, it should be considered when there has been an overdue error in the age of the passive subject. In this thesis, inductive, deductive, analytical, synthetic, exegetical, statistical and comparative methods were applied. Also, instruments such as: the survey and the interview. The results of applying such methods and instruments allowed to propose the project of legal reform to the Integral Penal Code, to incorporate among the paragraphs of Article 45, which deals with the mitigating circumstances of the penalty, one that contemplates the overdue error of type in the crime of statutory rape, induced by the passive subject to reduce the penalty of the person prosecuted.